A physical education teacher motivation from the self-evaluation framework. (March 2022) - Su, Jintao; Pu, Xiaoling; Yadav, Kusum; Subramnaiyan, Manikandan
Abstract: Motivation, whether in academia, physical activity, and sports, is essential to achieve. Therefore, the definition of motivation is to be understood and how different authors have defined the same. Knowledge of different motivational kinds is necessary to comprehend the actual significance of their meaning. Motivation needs an extensive investigation of its influence on physical education and athletics. Over the years, relatively little attention has been paid to physical education (PE) motivation. Self-determination theory (SDT) is an outstanding theoretical motivational model for understanding and argues that self-determined motivation derives from the perceived satisfaction of three psychological needs: autonomy, competence, and connection. The idea of self-determination says that humans are led to develop and evolve by three psychological demands that are fundamental and universal. This idea shows that people become self-determined when their competency, connection, and autonomy requirements are met. The proposed Self-Determination Theory for Physical Education (SDT-PE) technique offers a helpful platform for researching the psychological needs of PE teachers and their personal, professional, and environmental characteristics. The results revealed that a questionnaire on self-assessment is a legitimate and accurate means to evaluate the teacher's performance. In addition, this instrument can undoubtedly improve the teacher's knowledge, comprehension, motivation, and teaching attitudes.